Characteristics of air pollutant dispersion around a high-rise building. (September 2015) - Zhang, Y.; Kwok, K.C.S.; Liu, X.-P.; Niu, J.-L.
Abstract: A numerical wind tunnel model was proposed. The computed results of the pollutant diffusion around a typical Hong Kong high-rise building model (at a linear scale of 1:30), were found to show a similar trend to the outcomes of self-conducted experimental measurements that the pathways of pollutant migration for windward and leeward pollutant emission are different. For the case with windward pollutant emission at the 3rd floor within a re-entry, the pollutant migrated downwards due to the downwash created by the wind. In contrast, for the case with leeward pollution emission, dispersion is dominated by intense turbulent mixing in the near wake and characterized by the upward migration of the pollutant in the leeward re-entry. The simulated results of haze-fog (HF) studies confirm that the pathway of pollutant migration is dominated by wind–structure interaction and buoyancy effect only plays a minor role in the dispersion process. Graphical abstract: Highlights: A self-developed numerical wind tunnel model was proposed. Characteristics of air pollutant dispersion with windward/leeward emission were discussed. Wind–structure interaction controls the air pollutant dispersion around the building. Abstract : The different characteristics of air pollutant dispersion around a high-rise building, for both cases of a dispersion source in either the windward face or leeward face, are dominated by wind–structure interaction, with buoyancy effect playing only a minor role.